Modern weapons and military equipment for issue 2-2016 - Jevtić, Miloš M. (Vojnotehnički glasnik / Military Technical Courier, 2016)
Reflex sights as the tactical element of specialist equipment: About the creation, development and characteristics of modern design reflex sights, with an emphasis on the importance of the tactical use of these devices.